Analyzing the integration of Organization of Islamic Cooperation (OIC) countries before and during Rusian-Ukraine war - Haq, Daffa Aqomal; Nurhalim, Asep; Wiliasih, Ranti (IPB University, 2024)
Co-movement of integrated stock market is causing economic shocks and global crises. A typical example of this crisis was the Russia-Ukraine war in 2022, which impacted the stock market. Therefore, this research aimed to examine the development, integration, and response of the five Islamic stock market in Organization of Islamic Cooperation (OIC) countries during the Russia-Ukraine war. Vector Autoregressive/Vector Error Correction Model (VAR/VECM) was used to analyze DJIMMT25, SPSADS, SPSUUAEDS, JII, DJIMT, SPBMIR, and SPBMIU indices. The results showed that the United Arab Emirates (UAE) and Saudi Arabia stock market had the same movement, while Turkey experienced a positive trend during the war. The Islamic stock market was also cointegrated but Malaysia influenced the other four OIC countries. Meanwhile, IRF reported a permanent effect on the volatility of the market due to the shocks experienced. The volatility response was relatively small since the stock market dominated the contribution of shocks.